Emerging technologies, competing powers and disputed regions: Latin America and 5G in the technological contest between China and the United States - Colombo, Sandra [UNESP]; López, María Paz; Vera, Nevia (Pontificia Universidade Catolica de Minas Gerais, 2021)
This article focuses on the current technological dispute between the United States and the People’s Republic of China, emphasizing its impact at the Latin American level. More precisely, it analyzes the measures and pressures the United States are launching, faced with the implementation -real and potential- of Chinese 5G technology in Latin America, in an attempt to contain the technological primacy of the Asian giant over its historical area of influence and dominance. To achieve this, the article proposes the adoption of a qualitative approach to study two specific cases – Brazil and Argentina – through the analysis of articles, documents and journalistic notes. It concludes that, despite the growing expressions of this Sino-US bid regarding the implementation of 5G technology in Latin American territory, which pierces fundamental aspects such as security and technological autonomy, the countries of the region have yet to put this subject on their agendas. In particular, Argentina and Brazil have not been able to overcome their recent political differences, which weaken their negotiating capacity in this area.
Tecnologías emergentes, poderes en competencia y regiones en disputa: América latina y el 5G en la contienda tecnológica entre China y Estados Unidos
Tecnologias emergentes, potências concorrentes e regiões disputadas: América Latina e o 5G na confrontação tecnológica entre China e os Estados Unidos
Keywords: Argentina; Brazil; China; Technology; United States